2022
DOI: 10.26656/fr.2017.6(1).560
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and antibiofilm activity of Begonia multangula Blume. leaf extract against Candida albicans

Abstract: Candida albicans is a fungus that is included in the normal microbiota of humans. In general, C. albicans remains a lifelong commensal microorganism. This fungus has a hazardous impact. C. albicans can cause infection and is fatal. The spread of this fungus is one of the factors caused by antibiotic resistance, which causes C. albicans to be resistant and form strong colonies (biofilms) to survive. Natural ingredients for treatment is an alternative that is often used by the community because their use is effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…This result is in line with research by Hamzah, 2021, where it is known that Bajakah Tampala plant compounds provide activity faster than biofilm growth so that biofilm growth cannot form a complex structure and produces more extracellular polymeric substances (EPS) matrix which will provide a strong defense against S. aureus [20]. Another theory by Hamzah et al [21] also states that the mechanism of inhibition of biofilm growth can be by penetrating the bacterial cell wall so that it can interfere with communication signals (quorum sensing) between bacteria that play a role in biofilm formation or inactivate genes in bacteria that trigger EPS synthesis [10], so that the test results show a fairly high inhibitory activity. In addition, in the mid-phase of the biofilm, the ethanol extract activity of Bajakah Tampala was different for each concentration.…”
Section: Antibiofilm Activity Of Ethanol Extract Of Bajakah Tampala A...supporting
confidence: 87%
“…This result is in line with research by Hamzah, 2021, where it is known that Bajakah Tampala plant compounds provide activity faster than biofilm growth so that biofilm growth cannot form a complex structure and produces more extracellular polymeric substances (EPS) matrix which will provide a strong defense against S. aureus [20]. Another theory by Hamzah et al [21] also states that the mechanism of inhibition of biofilm growth can be by penetrating the bacterial cell wall so that it can interfere with communication signals (quorum sensing) between bacteria that play a role in biofilm formation or inactivate genes in bacteria that trigger EPS synthesis [10], so that the test results show a fairly high inhibitory activity. In addition, in the mid-phase of the biofilm, the ethanol extract activity of Bajakah Tampala was different for each concentration.…”
Section: Antibiofilm Activity Of Ethanol Extract Of Bajakah Tampala A...supporting
confidence: 87%
“…The concentration that can inhibit at least 50% of biofilm formation is considered Minimum biofilm inhibitory concentration (MBIC50). 23…”
Section: Antibacterial Activity Screening Test Of Telang Ternate Extractmentioning
confidence: 99%
“…In addition, many studies have shown that this plant contains phenolic compounds, flavonoids, steroids, terpenoids, and alkaloids (Karpova et al 2019;Bhattarai and Rana 2020). Furthermore, the compound contributes to antifungal and antibacterial activity (Siregar et al 2018;Tamam et al 2020;Hamzah et al 2022). Based on its potential and utility, B. multangula necessitates special attention to its botany, ecology, physiology, and genetic variation for conservation and development purposes.…”
Section: Introductionmentioning
confidence: 99%